ANALISIS STATUS TINGKAT LITERASI DIGITAL SISWA KELAS XI SMA N 1 KARANGANOM - Aswitasari, Rossa; Rosyada, Hayyi’lana Minamrina; Wonoseto, Muhammad Galih (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2023)
One of the skills students need in the 21st century is digital literacy. Digital literacy is the ability to understand and apply information from various digital sources. This study aims to measure the status of the digital literacy level of class XI students at SMA N 1 Karanganom. The research method used is quantitative descriptive. Data collection techniques through the distribution of digital literacy survey questionnaires. The dimensions of digital literacy analyzed in this study consist of 7 pillars of digital literacy, namely the pillars of information and data literacy; critical thinking pillar; pillar of communication skills; ethical pillars in technology; personal security pillars; device security pillar; and pillars of ability to use technology. The results showed that the highest percentage results were in the ability to use technology pillar with a percentage of 95.78% while the lowest percentage results were in the device security pillar with a percentage of 75.16%. This means that the majority of class XI MIPA SMA N 1 Karanganom have mastered and implemented the 7 pillars of digital literacy in everyday life.